y-3x=4
3y+2x=1
y-3x=4
3y+2x=1
To solve a system of equations by substitution, solve one of the equations for one of the variables, then plug that result into the other equation.
We want to solve equation 2 for y, so we need to eliminate the x from that equation.
Solve equation 1 for x in terms of y:
y-3x = 4
-3x = -y + 4
x = y/3 - 4/3
Replace the x in equation 2:
3y + 2x = 1
3y + 2(y/3 - 4/3) = 1
Now the equation only has the variable y and you can solve it.
The answer to the original question is:
y/3 - 4/3